MONITORING THE GOVERNMENT OF MEDAN’S LEGISLATIVE - Fitri Windari (Indonesian Journal of Multidisciplinary Science, 2022)
Planning is a key aspect in the stages of building and development of a region. The implementation of regional planning by the government and the Medan City secretariat is supervised by DPRD Medan City as part of the agency's supervisory responsibilities. The supervision carried out is an embodiment of the position of the DPRD, which is an element of the regional government together with the Medan City Secretariat. The supervisory function should be able to provide Medan city development planning that aspires to achieve community welfare. As well as uncover any abnormalities in the city's development planning process. The study was held at the Office of the Regional People's Representative Council (DPRD) Medan City. This research was conducted at the Medan City DPRD Office. This study uses a qualitative method, with the number of key informants being 9 people, representing 9 factions in the Medan DPRD. The findings of this study show that the supervisory function in the regional planning process is not fully and extensively controlled. In addition, this study should be utilized as a guide for members of the DPRD in carrying out their supervisory functions.